Abstracts of the 21st International Isotope Society (UK group) symposium: synthesis and applications of labelled compounds 2012. (25th February 2013) - Årstad, Erik; Badar, Adam; Baxter, Andrew; Bower, John F.; Cable, Karl M.; Carroll, Michael A.; Chan, Melanie Y. T.; Charlton, Michael; Christlieb, Martin; Cornelissen, Bart; Cox, Liam R.; Davis, Ben; et al.
Meeting Summary The 21st annual symposium of the International Isotope Society's United Kingdom Group took place at the Møller Centre, Churchill College, Cambridge, UK, on Friday 12th October 2012. The meeting was attended by around 60 delegates from academia and industry, the life sciences, chemical, radiochemical and scientific instrument suppliers. Delegates were welcomed by Dr Ken Lawrie (GlaxoSmithKline, UK, chair of the IIS UK group). The subsequent scientific programme consisted of oral and poster presentations on isotopic chemistry and applications of labelled compounds or of chemistry with potential implications for isotopic synthesis. Both short‐lived and long‐lived isotopes were represented, as were stable isotopes. The symposium programme was divided into a morning session chaired by Professor Chris Willis (University of Bristol, UK) and afternoon sessions chaired by Mr Mike Chappelle (Quotient Biosciences, UK) and by Dr Sofia Pascu (University of Bath, UK). The UK meeting concluded with remarks from Dr Ken Lawrie (GlaxoSmithKline, Stevenage, UK). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>